2021
DOI: 10.2147/jmdh.s288239
|View full text |Cite
|
Sign up to set email alerts
|

Ivermectin Treatment Coverage Validation in Two Onchocerciasis Endemic Districts in Ethiopia: A Community-Based Cross-Sectional Study, 2019

Abstract: Background: Onchocerciasis is the second leading cause of blindness globally next to trachoma, thus eliminating the infection is an important health priority. It is estimated that 15.7 million people are at risk of infection in different parts of Ethiopia. Mass drug administration with ivermectin at community and school level is the basis for control and elimination of onchocerciasis. This study was aimed at validating onchocerciasis treatment coverage in the selected districts of Ethiopia. Methods: A communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 9 publications
3
5
0
Order By: Relevance
“…In agreement with a recent coverage evaluation study conducted in Ethiopia [ 49 ] the survey coverage rates were 85.5% (95% CI: 83.6–87.2%) and 88.5% (95% CI: 86.7–90.1%) of the eligible population in Asosa and Yeki districts, respectively. Conversely, the current survey coverage rates were higher than the survey coverage rate reported from Foumbot and Massangam health districts inCameroon [ 45 ] and Abia state in Nigeria [ 50 ].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In agreement with a recent coverage evaluation study conducted in Ethiopia [ 49 ] the survey coverage rates were 85.5% (95% CI: 83.6–87.2%) and 88.5% (95% CI: 86.7–90.1%) of the eligible population in Asosa and Yeki districts, respectively. Conversely, the current survey coverage rates were higher than the survey coverage rate reported from Foumbot and Massangam health districts inCameroon [ 45 ] and Abia state in Nigeria [ 50 ].…”
Section: Discussionsupporting
confidence: 90%
“…This eventually resulted in failure to offer the medication to all eligible in need [ 42 ]. Consistent with findings of the current study, participants’ absenteeism from their respective homes or village at the time of drug distribution had been identified as a major reason for missing the drug [ 42 44 , 49 , 56 , 57 ]. In Yeki, though present in their homes and community, 14.9% (23/154) of the ivermectin non-recipients reported that they lack information about the MDA campaign.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Although targets for sustainable development include at least 4.45 trained health professionals per 1,000 population, many sub-Saharan Africa regions fell below the WHO guideline in which the minimum threshold level for greater accessibility of critical services and to minimize the risk of infection as a result of work overload is 2.3 health workers per 1000 population. 35…”
Section: Study Design and Settingmentioning
confidence: 99%